A Comparative Study of Using Science Subjects Laboratories Between Public and Private Preparatory Schools in Soran Administration - Hamad Ameen, Ara; Ibrahim, Omer (Humanities Journal of University of Zakho, 2022)
The research aims to compare the extent of using science subjects laboratories in public and private preparatory schools of Soran administration in the academic year (2021-2022). The study population was all science subjects teachers of preparatory schools in Soran administration. The sample was (115) science teachers in preparatory public and private schools with science laboratories. The samples were selected purposely, (91) science teachers in public preparatory schools and (24) science teachers in private preparatory schools. To achieve the objectives of the research, a questionnaire survey design has been utilized. The researchers have constructed an item-based scale as a research tool consisting of (49) items. The validity and reliability of the research tool have been conducted. After obtaining the data from the questionnaire, inferential statistical analysis was implemented by using a One-sample and Two-sample T-test. The research results have revealed that science teachers of public and private preparatory schools believe that using laboratories in teaching science subjects is crucial. However, private schools’ science teachers prefer using laboratories more than public schools’ science teachers. Besides, there is a significant difference between public and private schools in using science subjects laboratories, while the extent of using science subjects laboratories in private preparatory schools is more than in public preparatory schools of Soran administration. Based on the research results, the researchers have recommended that the Ministry of Education provide materials and essential facilities for Soran public schools’ laboratories and provide training courses for science teachers to learn how to utilize laboratories effectively and properly. Furthermore, the researchers have recommended that science teachers incorporate practical activities in their lessons and benefit from daily and simple materials to conduct scientific experiments. Finally, some further future studies have been suggested.